A formação em história no ensino médio a partir das competências da BNCC - Golinelli, Igor (2023)
The education of high school students on the field of history has always been based on the program content, inserted on the course plan. With the advent of the BNCC, a new learning perspective, based on competency-learning, has surfaced. It became imperative that teachers took ownership of this new model and discussed how to develop their work based on that perspective. This study analyzes how history should be taught in high school, based on the competencies proposed in BNCC, in its cognitive, values and attitudes, affective-emotional aspects and with regards to the development of students’ skills. The investigation was directed by the questioning of the possibility, power, and scope of competency-based learning, as proposed by the BNCC, and whether its practice would make the learning process more concrete. The methodology has a qualitative approach and is based on studies of theorists as well as practical experiences, based on a bibliographical and documentary base, aiming to understand in depth the possibilities of competency-based learning. The theoretical framework of the analysis will consider BNCC; and the works of Masetto, Sacristán and Perrenoud, in order to better comprehend the concept of competency, its application in education and its relationship with the learning process. We believe that the theoretical discussions of this research, as well as the observation of practice, will confirm that competency-based learning, unlike a traditional way of teaching, leads students to become critical, to act responsibly and with a sense of citizenship in the face of current issues, that is, to develop themselves as subjects integrally